Epidemiology of injuries in outdoor and indoor hockey players over one season: a prospective cohort study - Hollander, K.; Wellmann, K.; zu Eulenburg, C.; Braumann, K.-M.; Junge, A.; Zech, A. (British Journal of Sports Medicine, 2018)
Objectives: To determine the incidence and characteristics of hockey (`field hockey`) injuries over the course of one outdoor and indoor season. Comparisons of female versus male players, outdoor versus indoor season and match versus practice were performed.